Forest restoration by direct seeding: a global bibliometric analysis - de Souza, Diego C. [UNESP] (2022)
Direct seeding has been suggested to be a highly cost-efficient system for forest restoration but is still not applied on a large scale worldwide. Thus, to improve the knowledge surrounding the application of this system, I conducted a global bibliometric analysis about forest restoration by direct seeding. Based on a literature search of three online databases (Web of Science, Scopus, and Google Scholar), I found 81 peer-reviewed articles related to field experiments testing direct seeding for forest restoration. Each article was analyzed according to the following aspects: publication years, countries, continents, forest types, stages of restoration, journals, and authors. The results showed an increase in the number of articles published in recent years but a still low number of studies conducted to test the application of the system. These included field studies from a number of tropical and temperate countries worldwide, with a concentration of studies in Brazil and United States. Monitoring forests established by direct seeding is rare. A few researchers have paid special attention to the development of the field, and a few journals have published three or more articles on this topic. Overall, this study concludes that the application of direct seeding for forest restoration is a promising area for research, as the field is still little studied and has great potential to help achieve restoration goals. Furthermore, the results show trends and gaps that should be considered in future research to improve the application of direct seeding around the world.